Using text mining for personalization and recommendation for an enriched hybrid learning experience. (22nd April 2019) - Liu, Lei; Vernica, Rares; Hassan, Tamir; Damera Venkata, Niranjan
Abstract: Students are nowadays given many options to consume educational content in digital formats as alternatives to printed material. Previous research suggests that while digital content has advantages, printed media still provides other benefits that cannot be matched by digital. Therefore, technology should leverage the benefits of both. In this paper, we present the Meaningful Education and Training Information System, a multifaceted hybrid textbook learning platform. The goal of the system is to provide an easy digital‐to‐print‐to‐digital content creation and reading service. The Meaningful Education and Training Information System incorporates technologies for layout, personalization, cocreation, and assessments. These facilitate common teacher/student tasks and help provide a richer, more effective learning experience. Our system has been demonstrated in multiple international education events, partner engagements, and pilots with local universities and high schools.